National asbestos profile for Germany (Dortmund, 2014)
"At the Fifth Ministerial Conference on Environment and Health held in Parma, Italy, in 2010 the Member States of the WHO European Region adopted a declaration to develop national programmes for the elimination of asbestos-related diseases (ARDs) by 2015 in collaboration with WHO and the International Labour Organization (ILO). The National Asbestos Profile is an instrument to provide information to the member states. It defines the baseline situation with regards to the elimination of asbestos-related diseases, consumption of the various types of asbestos, populations at risk from current and past exposures. It also determinates the system for inspection and enforcement of exposure limits and the asbestos ban, and the social and economic burden of asbestos-related diseases. The aim of the National Profile is to work as a starting point for development and enforcement of national programs for the elimina-tion of asbestos-related diseases. It shall serve as an instrument to measure the pro-gress made towards the objectives and targets set by the national programs.